(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This article analyzes the issues of improving the property taxation mechanism in expanding the revenue base of local budgets. The study examines existing problems in the current taxation system, including shortcomings in property registration, valuation methods, and tax administration. It also highlights the role of property taxes in ensuring the financial sustainability of local budgets. Based on the research findings, scientifically grounded recommendations are proposed to expand the tax base, implement digital technologies, develop market-based valuation approaches, and improve tax administration mechanisms.